Design and Prototype Validation of a Laterally Mounted Powered Hip Joint for Hip Disarticulation Prostheses - Mroz, Sarah (Université d'Ottawa / University of Ottawa, 2023)
Powered prostheses are at the forefront of prosthetic technology, improving functionality by providing positive power to joints in the absence of native anatomy. Currently, there is no commercially available powered solution for hip-level amputees, and most hip prostheses are mounted to the front of the prosthetic socket. This thesis designed, fabricated, and tested a novel Laterally Mounted Powered Hip Joint (LMPHJ) that augments user gait to promote improved walking patterns. The LMPHJ attaches to the lateral side of the prosthetic socket, locating the hip centre of rotation closer to the anatomical location while ensuring user safety and stability. The new design locates the motor and all electronics in the thigh area, thereby maintaining a low profile while transmitting the required hip moments to the joint centre of rotation. A prototype was designed and manufactured to evaluate LMPHJ performance. Mechanical testing followed the ISO 15032:2000 standard and successfully demonstrated the joint's resistance to everyday loading conditions. Functional testing involved integrating the LMPHJ, Ossur Rheo Knee, and Ossur Pro-Flex XC with a prosthesis simulator that allowed three able-bodied participants to walk with the powered prosthesis successfully. This validated the mechanical design for walking over level ground and demonstrated that the LMPHJ is ready for next phase evaluation with hip disarticulation amputee participants.
Keywords: Prosthesis; Powered Hip; Hip Disarticulation; Microprocessor Controlled; Design; Validation